Training Utilizing Adobe After Effect In Advertising - Asbon Hendra Azhar; Ratih Adinda Destari; Bob Subhan Riza (STMIK Pontianak, 2021)
Along with the development of the times and technology requires everyone to have creativity and skills in him. Creativity and skills in the field of technology are a unity that go hand in hand and are indispensable in the world of work. For this reason, it needs to be instilled from an early age in directing and developing the skills and creativity of a student. By providing direction and guidance to students from an early age, it will help students in terms of learning and competition in the world of work. Adobe After Effects is a skillful skill that is rarely owned by everyone and needs to be introduced to students to help them do a creativity that will later be appreciated by companies or universities. Where every company needs a creative person to help work in the fields of design, animation, and multimedia, as well as universities. Universities really need teachers who are experts in the multimedia field.